2012
DOI: 10.1186/1477-9560-10-16
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA-126 in patients with coronary artery disease: correlation with LDL cholesterol

Abstract: BackgroundCoronary artery disease (CAD) is a major problem worldwide. Atherosclerosis and thrombosis underlying CAD involve multiple cell types. New and useful diagnostic markers are required. MicroRNAs (miRNAs) are a class of noncoding RNAs that posttranscriptionally regulate the gene expressions involved in various cellular processes. Endothelial dysfunction is implicated in early processes of athero-thrombosis. Thus, it was hypothesized that the level of vascular endothelium-enriched miRNAs would be altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 20 publications
8
73
0
3
Order By: Relevance
“…[17][18][19] However, the use of plasma miRNAs in gene expression studies faces technical limitations because of the extremely low concentrations of miRNAs freely circulating in plasma. Also, the absence of ribosomal RNAs in these samples makes the assessment of the RNA quality difficult.…”
Section: Stather Et Al Mirnas In Pad 491mentioning
confidence: 99%
“…[17][18][19] However, the use of plasma miRNAs in gene expression studies faces technical limitations because of the extremely low concentrations of miRNAs freely circulating in plasma. Also, the absence of ribosomal RNAs in these samples makes the assessment of the RNA quality difficult.…”
Section: Stather Et Al Mirnas In Pad 491mentioning
confidence: 99%
“…In particular, aberrant expression of miRNA-126 was found in patients with atrial fibrillation, heart failure and CAD 10,11 , suggesting a regulatory role of miRNA-126 in cardiovascular system. Therefore, we first investigated the role of miR-126 in atherosclerosis/CAD in this study.…”
mentioning
confidence: 99%
“…miR-33 an intronic miRNA is first reported with transcription regulator of sterol regulator binding gene SRBP2 involved in cholesterol metabolism (Rayner et al, 2010). Moreover, several other miRNAs including miR-92a (Loyer et al, 2014), miR-146a/b (Takahashi et al, 2010), miR-195 (Latranico et al, 2009, have been reported to have important regulatory roles in cardiovascular diseases. There are several miRNAs reported to have association with myocardial infarction (MI) like miR-126 associated with diabetes (Zampetaki et al, 2010), hyperlipodemia and age (Fukushima et al, 2011) the high levels of presence makes the patients with 2.7 fold higher risks of MI.…”
Section: Sumoylation and Inflammatory Pathwaymentioning
confidence: 99%